Intermittent feeding of citrus essential oils as a potential strategy to decrease methane production by reducing microbial adaptation. (1st September 2018) - Wu, P.; Liu, Z.B.; He, W.F.; Yu, S.B.; Gao, G.; Wang, J.K.
Abstract: The objective of the present study was to assess the effects of citrus essential oils (CEO) on growth and rumen fermentation of Hu sheep as well as to evaluate the effects of intermittent feeding of CEO to decrease methane production by reducing microbial adaptation in an in vitro batch culture system. Growth and rumen fermentation without CEO supplementation (W0_NE) and with supplementation with 0.8 mL CEO/L rumen volume from week 1 to week 3 (W1_EO, W2_EO, and W3_EO), as well as 2 additional weeks without CEO (W5_NE), were examined in 5 rumen-fistulated Hu sheep. Rumen fermentation and gas production of three substrates, corn meal (CM), Chinese wild rye hay (WH), and mixed feed (MF) of WH + concentrate (2:1, dry matter basis), and three doses of CEO (0, 0.8 and 1.6 mL/L) were tested in rumen fluid collected from W0_NE, W1_EO, W3_EO, and W5_NE in vitro . The results showed the CEO had no significant effects ( P  > 0.05) on body weight, average daily gain, dry matter intake and total-tract apparent digestibility. The CEO altered nitrogen metabolism and was characterized by reductions ( P  < 0.01) of the concentrations of blood urea nitrogen and rumen ammonia nitrogen. CEO decreased the concentrations of total and individual volatile fatty acids as well as the acetate to propionate ratio in vivo ( P  < 0.01). Anti-methanogenic effects of CEO were observed in W1_EO ( P  < 0.05) without additional CEO supplementation, but they were only observed in W3_EO and W5_NE with additional CEO supplementation. These results suggest that CEO introduce selective pressure on rumen microbes and induce methanogenesis adaptation in microbial communities. Intermittent feeding of CEO might be a potential strategy to decrease methane production by reducing the ability of microbes to adapt. Highlights: CEO had no significant effects on animal performance. CEO decreased of total volatile fatty acid concentration and acetate: propionate. CEO has anti-methanogenic effects, but induces methanogenesis adaptation. Intermittent feeding of CEO is a potential strategy to decrease microbial adaptation.